ETIKA APARAT PEMERINTAH TERHADAP KUALITAS PELAYANAN PEMBUATAN AKTA JUAL BELI TANAH DI KECAMATAN PANCA RIJANG - Monalisa Ibrahim; Efanita Udin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
This study aims to determine the ethics of government officials to the quality of service of making the deed of sale of land and determine the factors that influence the ethics of government officials to the quality of service of making the deed of sale of land in District Panca Chert. The design study is quantitative descriptive approach. The population in this study is the entire community that takes care of making the deed of sale of land in District Five Chert in January-December 2014 as many as 136 people. The samples in this study is Simple Random Sampling whereas the members of a sample of 58 people from a population of 136 people was randomly without regard to strata that exist in this population. Data collection techniques used were observation, interviews (interviews), Questionnaires, and a Research Library. The data obtained were then processed using frequency tables. The conclusion of this thesis research is ethical government officials classified in either category. Reflected in the results of this study which shows the scope of applicability of 57.33%. And quality of service are classified in either category. Reflected in the results of this study which shows the level of implementation of 57,60%. As for the temporary factors that influence the ethics of government officials to service quality land purchase deed, among others: (a) Awareness Officials, with the percentage rate of 53.5%. (B) Rules, with the percentage rate of 34.75%. (C) organization, with a percentage rate of 59.5%. (D) Skills Officer, with the percentage rate of 70.75%. (E) Support, with the percentage rate of 61.25%. (F) Supervision, with the percentage rate of 48.25%. (G) Consistency bureaucratic apparatus, with the percentage rate sebesar49,5%. (H) Communication, dengantingkat percentage of 58.25%.